Targeted Nanoparticles for Selective Marking of Neuromuscular Junctions and ex Vivo Monitoring of Endogenous Acetylcholine Hydrolysis - Mukhametshina, Alsu R; Fedorenko, Svetlana V; Petrov, Alexey M; Zakyrjanova, Guzel F; Petrov, Konstantin A; Nurullin, Leniz F; Nizameev, Irek R; Mustafina, Asiya R; Sinyashin, Oleg G (ACS applied materials & interfaces, 2018)
The present work for the first time introduces nanosensors for luminescent monitoring of acetylcholinesterase (AChE)-catalyzed hydrolysis of endogenous acetylcholine (ACh) released in neuromuscular junctions of isolated muscles. The sensing function results from the quenching of Tb(III)-centered luminescence due to proton-induced degradation of luminescent Tb(III) complexes doped into silica nanoparticles (SNs, 23 nm), when acetic acid is produced from the enzymatic hydrolysis of ACh. The targeting of the silica nanoparticles by α-bungarotoxin was used for selective staining of the synaptic space in the isolated muscles by the nanosensors. The targeting procedure was optimized for the high sensing sensitivity. The measuring of the Tb(III)-centered luminescence intensity of the targeted SNs by fluorescent microscopy enables us to sense a release of endogenous ACh in neuromuscular junctions of the isolated muscles under their stimulation by a high-frequency train (20 Hz, for 3 min). The ability of the targeted SNs to sense an inhibiting effect of paraoxon on enzymatic activity of AChE in ex vivo conditions provides a way of mimicking external stimuli effects on enzymatic processes in the isolated muscles.